OC-091 Uk experience of endoscopic ultrasound (eus) guided pancreatic fluid collection (pfc) drainage: review of 100 consecutive cases. (22nd June 2015) - Shekhar, C; Forde, C; Mahon, BS
Abstract : Introduction: Endoscopic ultrasound guided drainage is an effective, minimally invasive first line modality for the drainage of pancreatic fluid collection (PFC) resulting in a shorter hospital stay and less morbidity compared with surgical cystogastrostomy. 1 The revised Atlanta classification subdivides PFC more than 4 weeks old as either pancreatic pseudocyst (PP) or walled-off necrosis (WON). 2 Method: Retrospective reveiw of 100 consecutive EUS guided drainages of PFC was undertaken utilising EUS reports; clinical notes and imaging with follow up to 12 months. Technique: All procedures were undertaken under conscious sedation with EUS guidance alone (without fluoroscopy). After initial access, cystgastrostomy tract dilatation was carried with a 10F cystotome followed by balloon dilatation to 8 mm (6–15 mm) before placement of plastic double pigtail stents. Results: All procedures were undertaken at least 4 weeks after acute pancreatitis (AP). Alcohol (35%) and gallstone (32%) were leading causes of AP. Pain, signs of infection, weight loss and early satiety were most frequent indications for drainage. Of 76 cases of PP and 24 of WON, drainage was successful in 94 patients after 1 procedure and a total of 96 patients after 2 procedures comprising of (97% (77/79) in PP and 92% (22/24) in WON). Sign/symptoms of infection were present in 4% (3/76) PP and 42% (10/24) WON. Median size of cyst was 9 cm (3–23 cm). All but one case (93/94) had successful placement of 2 (1–3) 7Fr stents. Median interval for stent removal was 7 months (3.5–12 months). Stents fell out spontaneously in 2 patients. Symptoms improvement and cyst resolutionwas achieved in 94% (89/94) cases. 9% (8/94; 6 PP and 2 WON) required 2 further EUS guided dilatation of the tract and additional stent insertion. Immediate complications included bleeding: 4% (4/94) of which 1 required endoscopic intervention whilst 3 were treated conservatively; infection 4% (4/94, 2 requiring external drain) and leak in peritoneal cavity 1% (1/94, requiring external drain). In 4% further intervention was required: 1 WON (surgery) and 3 PP (CT guided external drain). There were no cases of cyst recurrence after stent removal. Conclusion: This is the largest series from a single UK centre demonstrating that EUS guided cystogastrostomy PFC drainage using plastic double pig tail stents is sufficient in high majority (96%) of cases with PFC including that of WON, with or without infection. It can be carried out under conscious sedation without propofol or general anaesthetic in the vast majority of cases with low morbidity. Disclosure of interest: None Declared. References: Gastroenterology 2013;145(3):583–90 Gut 2013;62:102–111